Analisis Uji Median K-Sampel Independen untuk Mengidentifikasi Jumlah Penduduk di Sumatera Utara - Septi Melani Putri Tambunan; Shalsha Nazillah; Talitha Nakhwan Hasibuan; Sisti Nadia Amalia (PT. Sharia Journal and Education Center, 2024)
This study aims to analyze the distribution of the population in North Sumatra using the Independent K-Sample Median Test on the 2023 data. The statistical test results show that there is no significant difference in the population numbers across the districts/cities in North Sumatra, with a Chi-Square value of 33 and a P-Value of 0.418, which is greater than 0.05. The Post Hoc analysis revealed that all groups have the same value, indicating a relatively even distribution of the population. Additionally, the overall median population in North Sumatra is 312,540, with minimal variation around this value. The study concludes that the population distribution in North Sumatra does not show significant differences among the tested groups.